Edukasi Gizi pada Ibu Hamil Mencegah Stunting pada Kelas Ibu Hamil - Ni Wayan Dian Ekayanthi; Pudji Suryani (Politeknik Kesehatan Tanjung Karang, 2019)
Stunting reflects the existence of chronic malnutrition problems, which influenced by the condition nutrition status of the prospective mother, during pregnancy, and baby 1000 first days of life (1000 HPK) It’s also influenced by health status on 1000 HPK. Stunting has a long-term adverse impact of declining cognitive ability and learning achievement decreased immunity and high risk for the emergence of diabetes, obesity, cardiovascular disease, cancer, stroke, and disability when they adults. It’s will lead to poor quality of work. Improvement efforts have needed for stunting prevention through specific nutritional interventions, particularly during pregnancy. Antenatal class is one measurement that can be used to disseminate information for behavior change relating to nutrition and healthiness during pregnancy to prevent stunting. This study aims to obtain the influence of the antenatal class toward knowledge and attitude improvement on stunting prevention. Pre-experimental design (one group pre-test post-test) with a sample of 35 first trimester pregnant women without complications, which are given antenatal class three times. Data retrieved with instruments of pre and post-intervention (antenatal class). Data were analyzed using a paired t-test for the knowledge variables and the Wilcoxon test for attitudinal variables. There was a significant influence of the antenatal class toward knowledge and attitude improvement on stunting prevention (p-value<0,05). The antenatal class increases pregnant women’s knowledge and attitude on stunting prevention.